2006
DOI: 10.1002/mrm.20937
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CBV measurement from static T1 changes in tissue and correction for intravascular water exchange

Abstract: The steady-state (SS) approach has been proposed to measure quantitative cerebral blood volume (CBV). However, it is known that the CBV value in SS (CBV SS ) is subject to error resulting from the effects of water diffusion from the intra-to extravascular space. CBV SS measurements were simulated in both fastand no-water-exchange limits, and compared with measured CBV SS values to determine which limiting case is appropriate. Twenty-eight patients were scanned with a segmented LookLocker echo-planar imaging (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 33 publications
3
87
1
Order By: Relevance
“…In this study, the effect of the CA might have been even smaller than in previous studies since the estimated ΔR1 in blood in this study was 2.2 s -1 (at a CA dose of 0.12 mmol/kg), while earlier studies showed values about 2-4 times higher after injection of 0.1 mmol/kg of CA [7,16]. The reason for this is not fully understood, but one possible explanation is that, in our study, a longer time delay between the bolus passage and the post-CA images, acquired at steady-state, were used.…”
Section: Estimation Of Cbvreferencecontrasting
confidence: 70%
See 4 more Smart Citations
“…In this study, the effect of the CA might have been even smaller than in previous studies since the estimated ΔR1 in blood in this study was 2.2 s -1 (at a CA dose of 0.12 mmol/kg), while earlier studies showed values about 2-4 times higher after injection of 0.1 mmol/kg of CA [7,16]. The reason for this is not fully understood, but one possible explanation is that, in our study, a longer time delay between the bolus passage and the post-CA images, acquired at steady-state, were used.…”
Section: Estimation Of Cbvreferencecontrasting
confidence: 70%
“…According to the Bookend concept, CBV can be obtained from T1 measurements before and after CA administration using the following equations [7,13]:…”
Section: Bookend Conceptmentioning
confidence: 99%
See 3 more Smart Citations